The Mental Health Consequences of Work-Life and Life-Work Conflicts for STEM Postdoctoral Trainees - Pitt, Richard N.; Taskin Alp, Yasemin; Shell, Imani A. (Frontiers in Psychology, 2021)
Research has shown that work-life conflicts exist among all kinds of workers, including academics, and these conflicts are a key contributor to workers’ reports of poor well-being. Very little research has been done on work-life conflict among post-baccalaureate PhD trainees (e.g., graduate students and postdoctoral trainees) who reside in an important liminal stage in the professoriate pipeline. In this study, we examine the degree to which postdocs believe they suffer from conflicts between their work responsibilities and their home responsibility and the relationship between those conflicts and postdoc’s mental health. We argue that, like other workers, postdocs suffer (in numerical terms and its relationship to health) more from the work-to-life imbalances than from life-to-work imbalances; life matters more than work, ultimately. Our results, based on a survey of 215 STEM postdoctoral trainees, reveal that a majority of postdocs say they have work-life conflicts and these work-life conflicts are associated with negative mental health outcomes. We discuss the potential impact of these findings on attempts to broaden participation in STEM careers and diversify the professoriate.